Quantifying the Incidence of Clinically Significant Respiratory Depression in Women With and Without Obesity Class III Receiving Neuraxial Morphine for Postcesarean Analgesia: A Retrospective Cohort Study. Issue 2 (24th June 2022) - Ende, H.B.; Dwan, R.L.; Freundlich, R.E.; Dumas, S.; Sorabella, L.L.; Raymond, B.L.; Lozada, M.J.; Shotwell, M.S.; Wanderer, J.P.; Bauchat, J.R.
Abstract : ( Int J Obstet Anesth . 2021;47:103187) Although neuraxial morphine is commonly administered to patients for analgesia following cesarean delivery (CD), one recognized side effect is respiratory depression. According to The Society for Obstetric Anesthesia and Perinatology (SOAP), obesity [body mass index (BMI) ≥40 kg/m 2 ] is a condition which increases the odds for respiratory depression and therefore necessitates enhanced respiratory monitoring for patients receiving neuraxial morphine. However, limited research has been carried out on the relationship between respiratory depression and obesity. To improve guidelines for respiratory monitoring for this patient population, the authors compared rates of respiratory depression in postpartum women with BMI ≥40 kg/m 2 to those of BMI <40 kg/m 2 . Specifically, the authors investigated the hypothesis that clinically significant respiratory depression following neuraxial morphine occurs more commonly in obese patients.